Spatial and Temporal Development of Müller Glial Cells in hiPSC-Derived Retinal Organoids Facilitates the Cell Enrichment and Transcriptome Analysis - Ning, Rong; Zheng, Dandan; Xie, Bingbing; Gao, Guanjie; Xu, Jinhai; Xu, Ping; Wang, Yuan; Peng, Fuhua; Jiang, Bin; Ge, Jian; Zhong, Xiufeng (Frontiers in Cellular Neuroscience, 2022)
Müller glial cells (MGCs) play important roles in human retina during physiological and pathological conditions. However, the development process of human MGCs in vivo remains unclear, especially how to obtain large numbers of human MGCs with high quality faces technical challenges, which hinder the further study and application of MGCs. Human induced pluripotent stem cell (hiPSC)-derived retinal organoids (ROs) with all retinal cell subtypes provide an unlimited cell resource and a platform for the studies of retinal development and disorders. This study explored the development of human MGCs in hiPSC-derived ROs and developed an approach to select and expand the induced MGCs (iMGCs). In ROs, retinal progenitor cells progressively differentiated into SOX9+ Ki67- MGC precursors during differentiation day (D) 60 to D90, while mature MGCs expressing markers CRALBP and GS gradually appeared since D120, which spanned the entire thickness of the neural retina layer. Cells isolated from ROs aged older than 120 days was an optimal source for the enrichment of iMGCs with high purity and expansion ability. They had typical features of human MGCs in morphological, structural, molecular and functional aspects, and could be passaged serially at least 10 times, yielding large numbers of cells in a short period. The transcriptome pattern of the expanded iMGCs was also revealed. This study firstly clarified the timecourse of human MGC development in the RO model, where the iMGCs could be enriched and expanded, paving the way for downstream investigation and application of MGC related retinal disorders.